The geographies of the dynamic evolution of Social networks for the flood disaster response and recovery - Karunarathne, Y. A.; Lee, Gunhak. (ELSEVIER, 2020)
Social networks and public supports have been becoming increasingly important in disaster management and mitigation. This paper demonstrates empirical and credible evidence of social network supports and their spatial and temporal dynamics of evolutionary patterns in flood disaster preparedness and recovery, as demonstrated by the case of the 2017 mass-flooding event in rural areas of Sri Lanka. For the case study, a number of flood- inundated households from several rural areas of Sri Lanka were selected for a questionnaire survey. Further- more, semi-structured interviews, focus group discussions, and field observations were conducted to collect empirical data regarding social networking for different phases of the flood. The results reveal the significant empirical finding that social support networks play a crucial role for flood disaster preparedness and recovery before, during, and after flooding events. Social networks also play a role in the provision of information, food, water, and other basic needs including evacuation and moving-out belongings, provision of shelters, and cleaning up contaminated houses and public places, which are helpfully exchanged for securing and reviving flood- affected livelihoods. More importantly, network characteristics have changed over time for disaster phases; additionally, evolutionary changes in network connections have occurred in different geographic settings.
Keywords: Evolution of social network; Spatial and temporal dynamics; Social network legacies; Flood disaster recovery; Sri Lankan flood; Disaster Risk Reduction; Sri Lanka